S76 Proteolytic Cleavage of Elafin by 20S Proteasome May Contribute to Inflammation in Acute Lung Injury. (19th November 2012) - Kerrin, A; Weldon, S; Chang, A; Craig, T; Simpson, AJ; O'Kane, C; McAuley, DF; Taggart, C
Abstract : The Aim: of this study was to characterise temporal changes in elafin concentration in patients with acute lung injury (ALI) and to evaluate whether a decrease in elafin levels is due to elevated protease activity. Previous work has shown that unregulated protease activity can cause proteolytic cleavage of elafin, impairing the innate immune function of the protein. Bronchoalveolar lavage fluid (BALF) was obtained from patients with ALI within 48 hours of onset of ALI (day 0), at day 3 and at day 7. Elafin levels were quantified by ELISA Elafin susceptibility to proteolytic cleavage by ALI BALF was assessed by Western blot and by HPLC-Mass Spectrometry. Elafin levels were found to be significantly increased at the onset of ALI compared to healthy volunteers and fell significantly by day 7 compared to day 0. In contrast, levels of secretory leukocyte protease inhibitor (SLPI) did not decrease over time. This decrease in elafin was due to cleavage by the 20S proteasome which was significantly increased in ALI BALF. Incubation of ALI BALF with the proteasome inhibitor epoxomicin confirmed that 20S proteasome protease activity was responsible for proteolytic cleavage of elafin resulting in diminished anti-elastase activity. In addition, free neutrophil elastase (NE) activity significantly increased in ALI BALF from day 0 to day 7. In conclusion, elafin concentrations decrease within the pulmonary compartment over the course of ALI as a result of proteolytic degradation. This loss of elafin may predispose, in part, to excessive inflammation in ALI.